Comparison of the mineralogy and microstructure of EAF stainless steel slags with reference to the cooling treatment - Loncnar M.; Mladenovič A.; Zupančič M.; Bukovec P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
TIn the present study the differences in the mineralogical composition and microstructure of various types of EAF stainless steel (EAF S) slag with regard to the cooling path, the operation practice in an EAF (electric arc furnace) and environmental ageing reactions were evaluated. It was shown that the mineralogy of the investigated EAF S slags varied from one slag to another, depending on the quality of the produced stainless steel. The production process of the treated steel also has a strong influence on the mineralogy of the slags. The conditions during water cooling were not sufficient to prevent the crystallization of primary mineral phases, which occurs predominantly in air-cooled EAF S slags, probably due to the high basicity of the investigated slags. However, the water cooling of hot slag leads to the absence of γ-CaSiO4 and the formation of secondary mineral phases predominantly calcite, portlandite, ettringite, calcium aluminate hydrate and calcium silicate hydrate. It has been shown that during the environmental ageing test (down-flow column test) secondary mineral phases were formed, which were the same as those formed during the water cooling of slags.